Improving Civics Learning Using Image Media in Class III at SD Negeri 008 Rambah Samo Kabupaten Rokan Hulu - Alirman Alirman (Indonesian Journal of Basic Education, 2023)
This Classroom Action Research was carried out in class III of SD N 008 Rambah Samo, Rokan Hulu Regency. This Classroom Action Research will start from August to October 2022, first semester of the 2022/2023 academic year. The subjects of this research were 21 students at SD Negeri 008 Rambah Samo. The results of teacher observations showed good improvements and changes from cycle I, meeting I to cycle II, meeting II, namely from 83, 86.89, 93 to reaching 93.33. Student learning outcomes show good improvements and changes from cycle I, meeting I to cycle II, meeting II, namely from 75, 79, 82 to 87. For schools, especially SD Negeri 008 Rambah Samo, it would be good to support teachers in finding creative ideas for educational learning. Citizenship in student learning